KONSTRUKSI MAKNA GERAK SEBAGAI KOMUNIKASI NONVERBAL DALAM MUSIK KONTEMPORER - Hanna Wisudawaty (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2018)
The research is conducted by researcher to identify and describe the meaning of kinesics in contemporary music for the composers. The research questions are: 1) How the contemporary musical composers interperet the kinesics messages through facial expressions. 2) How the contemporary musical composers interperet the kinesics messages through gestures. 3) How the contemporary musical composers interperet the kinesics messages through its artifactual. This research used a qualitative method with the interpretive paradigm through a phenomenological approach. Research subjects consisted of seven contemporary musical composers as informants taken purposively. In-depth interviews and field observations conducted in this research to gain the needed of research data. The results show that the composers of the contemporary music, the informants, construct the kinesics meaning in contemporary music subjectively. The variety of Kinesics meaning in every kind of contemporary musical creatures represents the confirmation of communication which has a different verbal expression. The theatrical type in the contemporary show must prominently be more dominant than instrumental type of the contemporary music show. The combinations of the three non-verbal Kinesics communication components, namely; facial, gestural, dan artifactual, deliver the results of the constructed kinesics meaning as follow: (1) The Kinesics messages in facial aimed to expresses the meaning of sadness, anger, and happy, especially through the composers mimic. (2) The kinesics messages in gestural aimed as a confirmation to communicating the dialog prominently through their body as expressed in the composers eyes, hands and lips movement. (3) The Kinesics messages in artifactual aimed to represent the identity as it is functioned as a ‘marker’ particularly through its dressing or costume, make up and through the instruments. Keywords: Contemporary Music, composers, non-verbal communication, Kinesics Meaning: Facial expressions, Gesture and Artifactual